Association of Viral Hepatitis with Different age Group - Naila Memon, Naseem, Sidrah, Kiran Memon, Aneela Faisal Memon, Kiran Aamir, Aamir Ramzan, Farhan Ahmed Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to determine the frequency of hepatitis B and C with different age groups. Study Design: Retrospective study Place and Duration: Medicine ward Liaquat university of Medical and health sciences jamshoro Hyderabad. Jan2022 to December 2022 Methods: Total 129 patients of both genders screened for hepatitis. Detailed demographic information, such as age, socioeconomic position, and place of residence, was recorded for enrolled cases after informed written consent was obtained. Antibody testing for hepatitis B virus (antiHBs) and hepatitis C virus (antiHCV) is conducted in a medical facility. Frequency of hepatitis with respect to age groups were identified. SPSS 24.0 was used to analyze all data. Results: In 129 patients, 74 (57.4%) were males and 55 (42.6%) cases were females. 87 (67.4%) patients had poor socio-economic status and 42 (32.6%) patients had high status. 79 (61.2%) patients were from urban residency. Among all, 70 (54.3%) patients were positive for HBV and 59 (45.7%) cases were positive for HCV. In 70 cases of HBV, 22 cases were aged between 3-15 years, 25 cases were aged between 16-30 years, 17 cases had age 31-45 years and 6 cases had age >45 years. IN 59 cases of HCV, 15 cases had age 3-15 years, 27 cases had age 15-30 year,13 cases had age 31-45 years and 4 cases had age >45 years. Conclusion: We concluded in this study hepatitis B was more prevalent among all cases as compare to HCV. Patients of age 15-45 years were diagnosed with higher number of viral hepatitis. It is crucial that community efforts to raise awareness of HBV and HCV and the value of vaccination continue unabated. Keywords: Hepatitis C, Hepatitis B, Gender, Age Group